REE AND Th MINERALS IN THE METASANDSTONES OF THE UDOKAN BASIN (RUSSIA) - E.V. Belogub; K.A. Novoselov; V.V. Shilovskikh; I.A. Blinov; E.E. Palenova (Минералогия)
Based on ICP-MS, optical and electron microscopy, and electron back-scatter diffraction data, the paper considers the distribution and the mode of occurrence of REEs and Th in metasandstones of the Lower Proterozoic Sakukan Formation, which host mineralization of the Udokan and Unkur copper sandstone deposits. The REE and Th contents increase in the layers enriched in iron oxides and minerals of natural heavy concentrate relatively to the background metasandstones. Detrital allanite is a major REE mineral, which occurs in layers enriched in iron oxides together with authigenic allanite, monazite, and unidentified Ca and REE carbonates. Thorium is concentrated in an authigenic silicate (thorite or thorogummite), which contains a significant amount of Fe, Ca, Al, and Cu and microinclusions of Cu and Pb sulfides and baryte. The diagenetic formation of authigenic REE and Th minerals is suggested as a result of desorption of these elements from siliceous-ferruginous gel-like sediments formed in river deltas and the wave-cut zone of the Proterozoic Sea.